COMPARISON OF AUTHENTICITY AND TRANSFORMATIONAL TRAITS BETWEEN NURSING STUDENTS LEVEL 1 TO 4 - Idauli Simbolon; Albinur Limbong; Mori Agustina Br Perangin-angin (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Today nursing students are the future leader. Based on behavioral theory, leaders are made. So, nursing college is one of the institutions that produce nursing leaders. There are 25 traits of successful leaders that can be learned and practiced in nursing schools. So, it is necessary for nursing schools to evaluate these leadership traits among the students. The study benefits the schools whether to maintain or revise the curriculum related to leadership and management courses. Objectives: This study aimed to describe and to compare nursing students’ Authenticity and transformational leadership traits between level 1 to 4. Methods: Comparative design was used in this study with the participation of 144 nursing students from level 1-4. Data are collected by using self-authentic and transformation questionnaire. Data are analyzed using SPSS descriptive and comparative analysis. Results: There are three Authenticity &Transformational traits that have been practiced as always by level 4 students who have working experience with the highest mean value of 4.0. They are fair, self-directed, and clear in communication & collaboration. There are different mean values of Authenticity &Transformational traits at each level of students. There are significant differences found in several levels. Conclusion: Based on the result, there is a big room for improvement in terms of practicing Authenticity &Transformational traits among nursing students. It is necessary for nursing schools to review and revise the leadership and management class instruction and activities in developing Authenticity &Transformational traits to a maximum level.